2018
DOI: 10.4103/2224-3151.228426
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delivery at home in Bhutan: findings from the National Health Survey 2012

Abstract: Lower socioeconomic status, rural location, eastern location, non- first birth, and having fewer than four antenatal visits were significant factors associated with home delivery. These findings should inform further research and policy to build on Bhutan's progress in promoting institutional delivery as the key strategy towards improving maternal and child health and achieving the relevant targets of Sustainable Development Goal 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Factors like cultural and religious beliefs might have been stronger in rural areas among marginalised groups. This finding is consistent with other studies [31,33].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Factors like cultural and religious beliefs might have been stronger in rural areas among marginalised groups. This finding is consistent with other studies [31,33].…”
Section: Discussionsupporting
confidence: 94%
“…We could not find any previous studies comparing factors associated with home delivery disaggregated by ethnicity in Nepal. However, several studies demonstrated statistically significant associations of home delivery with mothers age at birth [31], educational level of the mother [32][33][34], wealth status [31,33], province [33], place of residence [31,33], travel time to nearest health facility [32,34,35], and completion of four ANC visits as per national protocol [31,32,34,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with evidence indicated in Colombia, Nepal, Bangladesh, Zambia, and Kenya. 27,38 A study from Indonesia also indicated the same findings, women who have achieved higher levels of education were more likely to deliver at health facilities than those of lower educational status. 39 This implies that women have better access to health information and awareness about the negative consequences of not using skilled delivery care if they are educated.…”
mentioning
confidence: 80%
“…However, good knowledge on danger signs alone without easy access to health facilities would hinder receiving timely services. Geographical inaccessibility has been reported as a barrier to using ANC services in Bhutan [12] where women in rural areas were twice as likely to deliver at home than their urban counterparts [27].…”
Section: Reducing Maternal Mortalitymentioning
confidence: 99%